MEMORANDUm Februm 7 26 1991 Urban Resourc s Inc SUBJ F Mr Decemlr Activity Report During December 1990 Urban (Tufts Archival Research Center, 2007)
Activities report for December. Lists the actions taken by Urban Resources on behalf of the labor management committee. Mentions meetings with various labor officials and discussions regarding legsilation.